CONTROLLING FUNCTION OF A TAX IN INTERCONNECTION WITH ITS OTHER FUNCTIONS - Z. S. Yakupov (Russian Journal of Economics and Law)
Objective: to define and view the functions of taxes and taxation system. Methods: deduction and induction, scientific abstrcting, logical and statistical methods. Results: the carried out analysis of the existing hypotheses on finances and taxes has proved that tax functions are fulfilled bythe overall taxation system as a result systemic effect. Measures are suggested to improve the subsystems and elements of taxation system and tax administration as a whole. Scientific novelty: basing on the fact that the actual increase of control efficiency is possible only on condition of the increase of democratic institutions role in the society and establishing the state-private partnership, it is suggested to combine the advantages of state tax control with the potential of non-state controlling bodies, including audit and consulting organizations. During tax administration it is proposed to establish different approaches to large and small enterprises, because of their different roles in the society (strengthening of the tax control is needed in case of the large enterprises). Interdistrict inspections working with small businesses should obtain more freedom in choosing the types of tax control, to achieve their rational combination. Small business can become an experimental site for testing new approaches in tax administration. Practical value: possibility to increase tax control efficiency by involving audit organizations in tax inspections and other measures of tax control.